Can National Constitutions be Repealed and Enacted? An Appraisal of the Extensions or Limits of Legislative Powers - Ecoma, Bonnievolo Eson (Faculty of Law, Andalas University, 2024)
A constitution is the fundamental law of a country. Government institutions, including the legislature, are created and assigned definite functions through it. A central function of the parliament is law-making, and with this function goes the power to unmake or repeal laws. A fundamental question in light of this is whether the law-making and unmaking functions of the legislature extend to or are exercisable in respect of national constitutions to make for their repeal and subsequent enactment. Against this background and relying on the doctrinal research method, this paper appraises the legislature's law-making function to ascertain its extensions or limits where national constitutions are concerned.